Our relationship with the image as a form of being-with - Feinstein, K. * (2020)
This paper looks at the development of the artistic work from a narrative work into an experiential one. How the presentation of sublime in art has moved us away from finding meaning in narrative into taking on meaning through facing our relationship to the other. It traces how this change in communication has meant that the viewer’s experience with a work is the work. It takes an historical and theoretical perspective before discussing a proposed project, The Lamps of Presence, as a work employing these theories.